2016
DOI: 10.1590/1234.56781806-947900540209
|View full text |Cite
|
Sign up to set email alerts
|

Normativa de Produção Orgânica no Brasil: a percepção dos agricultores familiares do assentamento da Chapadinha, Sobradinho (DF)

Abstract: Resumo: O presente trabalho tem como objetivo determinar o grau de conhecimentos e aderência dos produtores familiares do assentamento rural Chapadinha, em Sobradinho (DF), às normativas de produção orgânica estabelecidas no Brasil. A metodologia de pesquisa utilizada contou com entrevistas abertas que pretenderam avaliar as percepções e conhecimentos dos produtores sobre as normativas mais importantes para a produção orgânica no Brasil: Lei n. 10831/2003; Decreto n. 6323/2007 e a IN n. 46/2011; as normas fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 2 publications
0
10
0
14
Order By: Relevance
“…MacInnis (2004) pointed out the lack of trade channels for organic products as a barrier to adherence to the organic system. In this research it was observed that, regarding the factor "organization of the supply chain", the aspects related to the distance between producer and consumer is one of the variables that can compromise the permanence of the producer in organic agriculture, since the producers often opt for marketing their products in short chains (MUÑOZ et al, 2016). In this case, the third-party or participative certification is unnecessary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MacInnis (2004) pointed out the lack of trade channels for organic products as a barrier to adherence to the organic system. In this research it was observed that, regarding the factor "organization of the supply chain", the aspects related to the distance between producer and consumer is one of the variables that can compromise the permanence of the producer in organic agriculture, since the producers often opt for marketing their products in short chains (MUÑOZ et al, 2016). In this case, the third-party or participative certification is unnecessary.…”
Section: Resultsmentioning
confidence: 99%
“…The study carried out with farmers from a rural settlement of Chapadinha, Distrito Federal -Brazil, through a case study with eight settlers who were in the process of obtaining the declaration issued through an SCO for the production and sale of organic products, pointed out the difficulty of producers in the understanding of the standards for certification, as explained in this article, namely Although producers meet the requirements for production and marketing of organic products, they are unaware of the bureaucratic issues involved in the certification process, from knowledge of standards to records procedures that are not performed. In this settlement, there are 42 settlers, of whom 23 obtained the declaration for direct sale of organic products (MUÑOZ et al, 2016). Furthermore, as Niederle (2014) points out, the requirements related to organic management practices are restricted and do not extend to traditional knowledge practices, which often leads to difficulties in adapting farmers to the certified system.…”
Section: Limiting Factors Related To the Certificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, vale ressaltar que, por possuírem o selo de certificação de orgâ-nicos, essas empresas recebem visitas periódicas (auditorias) da certificadora, que exige adaptações com relação ao processo produtivo, às embalagens e à distribuição, o que em um primeiro momento pode gerar despesas operacionais. De acordo com Muñoz et al (2016), a certificação por auditorias implica custos elevados e sofre influência de diversos fatores, como tamanho da área a ser certificada, elaboração de relatórios, análises laboratoriais, visitas, entre outros. "A auditoria trata-se de um instrumento empregado pelas empresas com o objetivo de auxiliar no atendimento à política, às práticas, aos procedimentos e aos requisitos legais, além de minimizar ou anular os impactos ambientais gerados" (Mazzarotto & Berté, 2013, p. 33).…”
Section: Gestão De Resíduos Na Produçãounclassified
“…A produção orgânica foi definida através de uma ratificação, sendo descrita como um sistema de produção que mantém a saúde do solo, das pessoas e dos ecossistemas substituindo a utilização de insumos com efeitos adversos; além disso, ela combina a tradição, inovação e ciência visando promover relações justas e boa qualidade de vida (MUÑOZ et al, 2016). Já a produção agroecológica é reestrutura em uma nova ordem para o curso social e ecológico, possuindo um caráter mais participativo e voltado para o social (GUZMAN; MOLINA, 1996).…”
Section: Introductionunclassified